2021
DOI: 10.3389/fncel.2021.768655
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Aberrant E3 Ligases Implicated in Alzheimer’s Disease and Development of Chemical Tools to Modulate Their Function

Abstract: The Ubiquitin Proteasome System (UPS) is responsible for the degradation of misfolded or aggregated proteins via a multistep ATP-dependent proteolytic mechanism. This process involves a cascade of ubiquitin (Ub) transfer steps from E1 to E2 to E3 ligase. The E3 ligase transfers Ub to a targeted protein that is brought to the proteasome for degradation. The inability of the UPS to remove misfolded or aggregated proteins due to UPS dysfunction is commonly observed in neurodegenerative diseases, such as Alzheimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 174 publications
(291 reference statements)
0
16
0
Order By: Relevance
“…CHIP has already been linked to various neurodegenerative diseases, such as polyQ disorders, Parkinson’s disease, and Alzheimer’s disease ( Miller et al, 2005 ; Kumar et al, 2012 ; Momtaz et al, 2020 ; Mylvaganam et al, 2021 ; Potjewyd and Axtman, 2021 ). In a transgenic SCA3 mouse model, it has been shown that reduction in CHIP leads to an increase in ataxin-3 microaggregates ( Williams et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…CHIP has already been linked to various neurodegenerative diseases, such as polyQ disorders, Parkinson’s disease, and Alzheimer’s disease ( Miller et al, 2005 ; Kumar et al, 2012 ; Momtaz et al, 2020 ; Mylvaganam et al, 2021 ; Potjewyd and Axtman, 2021 ). In a transgenic SCA3 mouse model, it has been shown that reduction in CHIP leads to an increase in ataxin-3 microaggregates ( Williams et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that multiple E3s are involved in AD-associated ubiquitination. In AD patients, various E3s, such as NEDD4-1, MARCH8, RNF192, Itch, and TRAF6, are reportedly upregulated and/or activated, whereas TTC3, Ube3A, CHIP, HRD1, and Parkin are downregulated ( Potjewyd and Axtman 2021 ). We reported that M1- and K63-ubiquitins are colocalized with thick bundles of tau NFTs from AD patients, while K48-ubiquitin is present in both tiny and thick inclusions ( Nakayama et al, 2019 ).…”
Section: Heterologous Ubiquitin Chains In Neurodegenerative Disease I...mentioning
confidence: 99%
“…For example, no pathogenic protein, such as mutated SOD-1 protein or TDP-43 protein, can be targeted by a PROTAC in ALS patients. On the other hand, the crystal structure analysis of TDP-43 guided the development of the TDP-43 ligand, which is expected to be used for the development of a PROTAC targeting TDP-43 degradation …”
Section: Targeted Protein Degradation For Neurodegenerative Disease T...mentioning
confidence: 99%
“…On the other hand, the crystal structure analysis of TDP-43 guided the development of the TDP-43 ligand, which is expected to be used for the development of a PROTAC targeting TDP-43 degradation. 98 3.2. Trim-Away for Neurodegenerative Disease Therapy.…”
Section: Protacs For Parkinson's Disease Therapymentioning
confidence: 99%